ANALISIS PENINGKATAN KESEJAHTERAAN NASABAH TERHADAP PEMBIAYAAN MURABAHAH (Studi Kasus Bank Aceh Syariah Capem Krueng Geukueh) - Maulida Mahdalena; Suryani Suryani; Ismaulina Ismaulina (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2021)
This study aims to determine differences in income before and after getting murabaha financing at Bank Aceh Syariah Capem Krueng Geukueh. The research method uses quantitative methods with a sample of 45 respondents. Data collection was carried out using a Likert scale questionnaire. Based on the results of the study there is a relationship between welfare and cheap financing at Bank Aceh Syariah Capem Krueng Geukeuh, with the difference in the difference in average income before and after amounting to -8,587 to -7,635. This research is useful for researchers themselves, for banks, for murabaha financing customers, and for future researchers. Keywords: welfare, income and murabahah financing